Educação patrimonial na formação inicial de professores: um estudo acerca das percepções dos gestores dos Cursos de Licenciatura da Universidade Estadual do Maranhão. - COELHO, Samary Pinheiro (2021)
The current conjuncture of society in terms of learning has the necessity of Higher Education Institutions (HEIs) to create spaces for ruptures, transformations and constructions of a democratic society with trained and qualified in all human aspects. In the perspective of change, the teacher plays a fundamental role in the student's life. As a result, it is necessary to design educational actions for the training and qualification of future teachers, capable of providing a better understanding of reality and effective participation in social, political and cultural relations, which are increasingly broad and diverse. The main objective of this research was to investigate in the curricula of undergraduate courses at the State University of Maranhão (Uema), Campus of São Luís, an approach and incorporation of themes related to heritage education and its contribution to the promotion of the valorization, identification and preservation of the cultural heritage. Methodologically, the study was organized through bibliographic, documentary and field research, aiming at the preparation of a systematic study about the theoretical assumptions about cultural heritage, heritage education and teacher training; identification of references in the Institution's documents on the inclusion of topics related to heritage education and; description of the perception of managers of undergraduate courses about heritage education as part of the educational process at the Institution, led by approaches to understandings encompassing the perception of heritage issues; the perception of the current curriculum of the course and the perception of continuing education. Finally, it concludes that themes arising from cultural heritage, through a transversal approach, constitute one of the ways of forming educative awareness in teaching. In order to offer methodological subsidies to work on cross-cutting themes in higher education, a research led to the elaboration of the Guide for guidelines for the implementation of cross-cutting themes in higher education, focusing on heritage themes.